Surface plasmon resonance to trace and measure cancer cell apoptosis using morphological and refractive index changes - Rais, Nor Akmaliza; Abouhajar, Fatimah; Stuart, Daniel D.; Van Zant, Westley; Cheng, Quan (Frontiers in Analytical Science, 2024)
Morphological changes of cancer cells are often used as an important indicator within efficiency studies of anticancer drugs. Morphological cell analysis on cell size and shape distribution is typically performed using microscopic methods, which are time consuming and require skilled personnel. Recently, more advanced image processing and pattern recognition have enabled identification and quantitative analysis of the cell’s abnormality and classification in an automated way. However, these methods usually involve multiple staining steps. In addition to computational complexity, the processes greatly compromise real-time applications of the system. Therefore, a non-invasive, real-time method allowing for assessment of living cells’ reactions to a death inducer is very much needed. Here, we present an SPR biosensor that measures the changes in cancer cells’ size and detachment, relating the cell confluency with the changes of the refractive index on the cell-substrate interface. As a proof-of-concept, we chose HeLa cell and hydrogen peroxide (H2O2) induced apoptosis as the model system to study the morphological changes of the cell. The results show that the SPR response to cell apoptosis agreed with the cellular morphological changes observed via microscopy. Interestingly, we observed simultaneous apoptosis and necrosis at high H2O2 concentrations. This simultaneous occurrence was verified using a mathematical model which incorporated other important factors such as cell thickness and intercellular refractive index. This model helped resolve the disagreement between SPR signal and cell confluency at high H2O2 concentrations. Our results show the potential of SPR as a label free and real time monitoring method for morphological changes and surface detachment of cancer cells. This method can be fully expanded to other cell-based sensing applications.